Color and surface gloss stability of bis-acryl and resin composite after exposure to cigarette smoke - Rocha, Rafael Santos [UNESP]; Ruano, Victor [UNESP]; Souza, Maurício Yugo de; Salomão, Fabio Martins; Bresciani, Eduardo [UNESP] (Editora Cubo, 2022)
Objective: To evaluate color and surface gloss stability of bis-acryl resins and resin composites, submitted to artificial staining with cigarette smoke. Material and Methods: Specimens of each material were prepared (n=15). Two resin composites (GrandioSO [RCG], Filtek Supreme [RCZ]) and five bis-acryl resins (Luxatemp Star [BisLUX], Protemp4 [BisPRO], Structor3 [BisSTR], Visalys Temp [BisVIS] and Yprov [BisYPR]) were tested. Initial color was assessed using a spectrophotometer and surface gloss with a glossmeter. Samples were submitted to smoke exposure (10 cigarettes under 8 minutes per cycle). After 3 and 6 cycles, color and gloss were reassessed. Final readings were performed after brush prophylaxis. Data were analyzed using two-way repeated ANOVA and Tukey’s test (p<0.05). Results: Differences and interaction of factors (p<0.01) were detected for both color and gloss readings. Resin composites were the least affected by aging, with gloss reduction after prophylaxis. Differences were detected among bis-acryl resins, with better results for BisLUX and BisPRO. BisPRO and BisSTR, showed reduction in gloss after 60 cigarettes, while BisYPR gloss decreased at all evaluated periods. Conclusion: Resin composites are less susceptible to changes after smoke exposure, while bis-acryl resins results are brand-dependent. Prophylaxis negatively influenced the surface gloss of most of the tested materials.
Estabilidade de cor e brilho superficial de resinas compostas e bisacrílicas após exposição por fumaça de cigarro
Keywords: Bis-acryl resins; Color; Composite resins; Smoke; Temporary dental restoration